Comparative Anthropometric Assessment of Facial Asymmetry between Patients with and without External Nasal Deformity - Baidya, Smriti; Thapa, Narmaya; Gurung, Urmila (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Facial symmetry is determining the attractiveness of the face. It must be taken into consideration and not just the nose in isolation for patients seeking rhinoplasty. It may however exist even in absence of external nasal deformity. Aim: The study was conducted to compare the nature of facial asymmetry and its frequency in patients with and without external nasal deformity. Methods: This observational, analytical study was conducted from September 2020 to October 2021 in the Department of Ear Nose and Throat (ENT) – Head and Neck Surgery, Tribhuvan University Teaching Hospital (TUTH), Maharajgunj Medical Campus Institute of Medicine, Nepal. Frontal photograph of patients seeking rhinoplasty for external nasal deformity was compared with patients without external nasal deformity visiting ENT Out Patient Department (OPD) for other complaints. Anthropometric measurements based on soft tissue landmarks, starting with an imaginary line from the midpoint of the hairline, crossing midpoint of the nasal bridge, the central point of cupid’s bow, upper lip, and lowest midpoint of the chin were measured. Distance between this line and medial canthus, lateral canthus, lateral alar margin, oral commissure, and tragus were measured and the means of the ratios were compared. Results: The mean of the ratio of the midline to lateral alar margin showed a significant difference (p<0.040) with regards to facial asymmetry in patients seeking rhinoplasty for external nasal deformity. Objectively, all the patients had some degree of asymmetry in both groups. Conclusion: Facial asymmetry was found in both patients with and without external nasal deformity indicating that facial asymmetry is a common entity irrespective of external nasal deformity.